The Efficacy of a Novel Water-Soluble Anti-Mycotoxin Solution in Improving Broiler Chicken Performance Under Mycotoxin Challenge - Sayantani Sihi Arora; Anusuya Debnath; Amrita Kumar Dhara; Sudipto Haldar; Raquel Codina Moreno; Insaf Riahi (Toxins)
Mycotoxins like aflatoxins (AFs), fumonisins (FBs), and ochratoxin A (OTA) pose serious health risks to humans and animals. Fruit pomace extracts, rich in natural nutrients and bioactive compounds, have the potential to enhance animal health and mitigate mycotoxin toxicity. This study evaluated a novel liquid anti-mycotoxin solution (LAS), a combination of grape and olive pomace extract administered to broiler chickens through drinking water (2 L:1000 L) for 1–42 days under a natural multi-mycotoxin challenge. The 42-day trial with 288 one-day-old male Ross 308AP95 chicks included four experimental groups: a negative control (NC); NC+LAS; a positive control (PC) group fed a diet containing 80 μg/kg AFs, 1600 μg/kg FBs, and 50 μg/kg OTA; and PC+LAS. The growth performance, oxidative defense genes (liver), and stress biomarkers (blood) were analyzed. Mycotoxin exposure negatively affected body weight (BW), the feed conversion ratio (FCR), and the oxidative defense mechanism. LAS supplementation improved BW and the FCR, reduced Nrf-2 expression, and enhanced mycotoxin detoxification via lower EPHX1 expression. Though the LAS did not fully restore performance to NC levels, it significantly mitigated mycotoxin-induced damage. This study concluded that the LAS is a promising solution to improve broiler resilience against moderate to high mycotoxin exposure.